Advantages and problems of combining GPS with GLONASS - Swann, John W. (1999)
The Global Positioning System (GPS) has been an undoubted success and a great many applications have benefited from it. It does however have limitations, which make its use in certain environments, and for certain tasks, difficult or indeed impossible.In recent years a second satellite based navigation system, the Global'naya Navigatsionnaya Sputnikov Sistema (GLONASS) has become increasingly available. A great deal of interest has been expressed in combining both these systems, in the hope that combined GPS/GLONASS technology will present significant benefits under conditions where GPS alone has struggled.